Pendidikan Tasawuf Sebagai Strategi Meningkatkan Kecerdasan Emosional Siswa di Tingkat Dasar - Fatimatus Zahro Rafika Sari; Erly Sintya Putri; Putri Aualia Reviana; Muhammad Romadhon Habibullah (Kampus Akademik Publiser, 2025)
In the modern educational landscape, emotional intelligence is a key component of students' academic and social success. Amid the challenges of globalization and technological advancement, elementary school students are not only required to excel intellectually but also to develop the ability to manage emotions, empathize, and build strong social relationships. Sufi education, rooted in spiritual and moral values, offers a holistic approach to character building and fostering emotional intelligence from an early age.This research aims to explore how the implementation of Sufi education in elementary schools can contribute to enhancing students' emotional intelligence. The study employs a qualitative research method, with the subjects being teachers and second-grade students at MI Ummi Kamilah Sunan Drajat Bojonegoro.The findings reveal that the implementation of Sufi education at MI Ummi Kamilah Sunan Drajat is conducted through daily activities such as collective prayers and the cultivation of noble character. These practices have been proven to create a calmer and more harmonious learning environment while enhancing students' self-awareness. Sufi education also aids students in managing their emotions, improving social skills, and fostering perseverance in overcoming learning challenges.